GIANT CUTANEOUS HORN - Kumaresan, M (Medknow Publications, 2008)
A 53-year-old male presented with a giant cutaneous horn over the left leg. Cutaneous horn was excised and primary closure of the defect was done under spinal anesthesia. Histopathology showed underlying seborrheic keratosis. Cutaneous horn has been noticed on top of many clinical conditions of diverse etiology, such as actinic keratoses, wart, molluscum contagiosum, seborrheic keratoses, keratoacanthoma, basal cell and squamous cell carcinoma. We report a patient with giant cutaneous horn on the leg successfully treated by excision and wound closure.